(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Reading plays a crucial role in both academic achievement and cognitive development. It enhances attention, working memory, and metacognitive skills, enabling learners to monitor understanding, evaluate information, and reflect on meaning. Engagement with diverse texts—ranging from argumentative and scientific materials to fiction—fosters critical and creative thinking, strengthens problem-solving abilities, and promotes empathy and perspective-taking. Furthermore, reading enriches vocabulary, supports syntactic awareness, and improves verbal reasoning, contributing to more effective communication. This article examines how reading cultivates these cognitive and academic skills, highlighting its significance in preparing individuals for complex learning tasks and lifelong intellectual growth.